Effect of 40 Hz Magnetic Field Application in Posttraumatic Muscular Atrophy Development on Muscle Mass and Contractions in Rats. Issue 8 (7th December 2022) - Cicek, Figen; Tastekin, Bora; Baldan, Ilknur; Tokus, Murat; Pelit, Aykut; Ocal, Isil; Gunay, Ismail; Ogur, Hasan U.; Cicek, Hakan
Abstract : Muscle atrophy refers to the deterioration of muscle tissue due to a long‐term decrease in muscle function. In the present study, we simulated rectus femoris muscle atrophy experimentally and investigated the effect of pulsed electromagnetic field (PEMF) application on the atrophy development through muscle mass, maximal contraction force, and contraction–relaxation time. A quadriceps tendon rupture with a total tenotomy was created on the rats' hind limbs, inhibiting knee extension for 6 weeks, and this restriction of the movement led to the development of disuse atrophy, while the control group underwent no surgery. The operated and control groups were divided into subgroups according to PEMF application (1.5 mT for 45 days) or no PEMF. All groups were sacrificed after 6 weeks and had their entire rectus femoris removed. To measure the contraction force, the muscles were placed in an organ bath connected to a transducer. As a result of the atrophy, muscle mass and strength were reduced in the operated group, while no muscle mass loss was observed in the operated PEMF group. Furthermore, measurements of single, incomplete and full tetanic contraction force and contraction time (CT) did not change significantly in the operated group that received the PEMF application. The PEMF application prevented atrophy resulting from 6 weeks of immobility, according to the contraction parameters. The effects of PEMF on contraction force and CT provide a basis for further studies in which PEMF is investigated as a noninvasive therapy for disuse atrophy development. © 2022 Bioelectromagnetics Society.